FRI0319 Predictors of complete remission in polymyalgia rheumatica. (15th June 2017) - Birra, D; Zoli, A; Peluso, G; Bosello, SL; Gremese, E; Ferraccioli, G
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory rheumatic condition characterized by aching and morning stiffness in the shoulders, hip girdle, and neck that typically occurs in adults over the age of 50. A rapid resolution of symptoms with low-dose glucocorticoids is a feature of PMR although some patients may experience a disease flare-up during steroid tapering. Objectives: The aim of the study was to investigate possible clinical or laboratory prognostic factors of remission during a 12 month follow up in PMR patients treated with a starting low prednisone dose following the 2015 ACR-EULAR guidelines (1) . Methods: From 86 consecutive outpatients, diagnosed with PMR following ACR/EULAR 2012 provisional clinical criteria for PMR (2), 79 patients (56 women and 23 men), that achieved a complete follow up of at least 12 months, were selected. Clinical evaluation and laboratory tests were performed every 3 months Clinical remission was defined as lack of shoulder and hip girdle pain and as levels of ESR≤40 mm/h and CRP≤0.5 mg/dl. Results: 37 PMR patients reached a complete remission after twelve months follow-up. We didn't find any significant difference in the mean age and in ESR and CRP values at the beginning of the disease in patients in remission after 12 month of follow up when compared with patients not in remission. Presence of obesity, dyslipidemia, hypertension, diabetes and smoking habits were not significantly different in the two groups of patients. No significant difference in steroid therapy at the beginning and after 6 month of follow up was noted between the two groups of patients. A statistically significant female low clinical remission was seen at the end of 12 month follow up when compared with male complete clinical remission (33.9% versus 78.2%, p=.000) Moreover it was shown that the patients achieving clinical and laboratory remission after six months of therapy were also those who maintained remission at the 12 month. CRP values, instead of ESR ones, were more predictive of remission after one year of therapy. Therefore patients with clinical remission in the absence of normalization of CRP value had greater risk of exacerbation. Conclusions: The sixth month of therapy is a crucial target for the management of PMR, because it can help to identify patients at greater risk of exacerbations, which may benefit from a tighter follow-up and a more aggressive therapeutic strategy. Among prognostic factors female sex and high CRP values at sixth months appear to be associated with higher relapse risk and a longer duration of treatment. References: Dejaco C, Singh YP, European League Against Rheumatism; American College of Rheumatology, 2015 Recommendations for the management of polymyalgia rheumatica: a European League Against Rheumatism/American College of Rheumatology collaborative initiative. Ann Rheum Dis. 2015 Oct;74(10):1799–807. doi: 10.1136/annrheumdis-2015-207492. Dasgupta B, Cimmino MA, Matteson EL. 2012 provisional classification criteria for polymyalgia rheumatica: a European League Against Rheumatism/American College of Rheumatology collaborative initiative, Ann Rheum Dis. 2012 Apr;71(4):484–92. doi: 10.1136/annrheumdis-2011-200329. Disclosure of Interest: None declared